Approximation of the classes C_β^ψ H_ω by generalized Zygmund sums - Ovsii, E. Yu.; Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We obtain asymptotic equalities for the least upper bounds of approximations by Zygmund sums in the uniform metric on the classes of continuous 2π-periodic functions whose (ψ, β)-derivatives belong to the set H_ω in the case where the sequences ψ that generate the classes tend to zero not faster than a power function.